Effect of probiotics on the obese patient. A review study - Montachana Crespata, Milena Alexandra; Viteri Robayo, Carmen Patricia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: the gut microbiota is a potential determining factor in the development of obesity, resulting in dysbiosis, which is related to a lower number of members of the Bacteroidetes division and an increase in Firmicutes leading to a decrease in energy expenditure, it is also associated with the inflammatory process, insulin resistance and type 2 diabetes mellitus. Objective: to conduct a literature review related to the effects of probiotics on the improvement of the intestinal microbiota in an obese patient and its associated disorders.Methods: a search of articles in PubMed, Google Scholar and Elsevier from the last five years was conducted using the terms "obesity and probiotics", "effect of probiotics", "gut microbiota and probiotics". A total of 23 articles were included in the selection criteria.Results: supplementation with probiotics specifically certain strains such as Lactobacillus plantarum and Bifidobacterium could lead to significant weight reductions, in combination with energy restriction and physical activity. However, it is important to develop clinical trials that are properly designed, including all aspects of lifestyle, gut microbiota, metabolites, and genetic background.Conclusions: despite the beneficial effects, they are not yet considered an alternative strategy in the treatment of obesity due to the lack of research in this field, since the currently available data come from studies conducted in animals that may not present potential in humans. It is important to conduct more large-scale longitudinal studies with longer follow-up.